3D thickness profile measurement of thin films coated on the microscopic area. (6th May 2015) - Joe, H-E; Min, B-K
Abstract: Film thickness profile measurements are crucial in manufacturing processes of thin film–based devices that require precisely controlled thickness and surface morphology. However, film thickness measurement techniques, such as scanning electron microscopy, transmission electron microscopy, and ellipsometry, are limited to 1D or 2D analyses. We propose a new method to measure 3D thickness profiles. The resulting profiles contain not only the thin film surface morphologies but also 3D thickness data. The proposed method includes direct surface measurements and an alignment process utilizing fiducial marks. The top and bottom surface profiles of the film are directly measured using atomic force microscopy before and after a selective etching process. The proposed method based on simple principles including surface measurement and alignment processes is capable of evaluating films that are too thick to be measured using optical methods.